Natural desiccated thyroid for the treatment of hypothyroidism? - Heald, Adrian H.; Taylor, Peter; Premawardhana, Lakdasa; Stedman, Mike; Dayan, Colin (Frontiers in Endocrinology, 2024)
Primary hypothyroidism affects about 3% of the general population in Europe. Early treatments in the late 19th Century involved subcutaneous as well as oral administration of thyroid extract. Until the early 1970s, the majority of people across the world with hypothyroidism were treated with natural desiccated thyroid (NDT) (derived from pig thyroid glands) in various formulations, with the majority of people since then being treated with levothyroxine (L-thyroxine). There is emerging evidence that may account for the efficacy of liothyronine (NDT contains a mixture of levothyroxine and liothyronine) in people who are symptomatically unresponsive to levothyroxine. While this is a highly selected group of people, the severity and chronicity of their symptoms and the fact that many patients have found their symptoms to be alleviated, can be viewed as valid evidence for the potential benefit of NDT when given after careful consideration of other differential diagnoses and other treatment options.